The influence of communication on project success - Zainab Aziz (Communicare)
In any successful project, communication plays a significant role and forms the basis to ensure effective project results. Only a few studies in South Africa have considered the influence of communication on the perceived success of a project. Thus, this research investigates the influence and explores the role of communication in project management success within the case example of Gauteng’s SANRAL e-toll project in South Africa. This study highlights some of the areas in the project communications processes. The practical importance of the study shows that communication is the key to effective project management. The research design of this correlational and exploratory study entailed a positivist research philosophy using a deductive approach. The quantitative research was conducted by means of a survey questionnaire. A questionnaire was designed and used to determine the level of influence of communication on stakeholders in the case example of Gauteng’s SANRAL e-toll project. A qualitative study was conducted by means of a semi-structured interview. An interview guide was designed and used to determine insight about Gauteng’s SANRAL e-toll project. The answers provided on these questions were then analysed to determine how project communications might contribute to the outcome of projects.